2005
DOI: 10.1080/00207450590524340
|View full text |Cite
|
Sign up to set email alerts
|

Specific Circular Organization of the Neurons of Human Interthalamic Adhesion and of Periventricular Thalamic Region

Abstract: Interthalamic adhesion between the medial surfaces of the left and right thalamus is a variable structure and contains the midline thalamic nuclei, which are not much developed in humans. The research has been done on 6 human brains obtained during routine autopsy (age 45 to 65; 4 male and 2 female). Every tenth 10 microm thick frontal section was stained according to Klüver-Barrera method. In all cases the authors found a specific organization of certain groups of neurons within the interthalamic adhesion (IA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
6
1
1
Order By: Relevance
“…Laslo et al (2005) reported a specific circular organization of the neurons contained within the ITA that could represent in-vivo correlates of neurospheres and the Golgi morphology comprising these neurons tends to be highly variable across individuals, but with fusiform neurons being the most characteristic (Malobabic et al 1990). Several features of the ventricular system, including the ITA do not become apparent until the fetal period, around the second trimester of gestation (O’Rahilly and Müller 1990; Rosales et al, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Laslo et al (2005) reported a specific circular organization of the neurons contained within the ITA that could represent in-vivo correlates of neurospheres and the Golgi morphology comprising these neurons tends to be highly variable across individuals, but with fusiform neurons being the most characteristic (Malobabic et al 1990). Several features of the ventricular system, including the ITA do not become apparent until the fetal period, around the second trimester of gestation (O’Rahilly and Müller 1990; Rosales et al, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Interthalamic adhesion is little related in neuroimaging [19], but there are studies of magnetic resonance, that it extends further in males than in females [20]. In postmortem studies, it has been found that, between 15% and 30% of cases, the structure never develops, as a variation of normality [21]. It may swell throughout various illness processes, a fact which was made evident in the postmortem studies of individuwww.acbjournal.org https://doi.org/10.5115/acb.21.164 als who suffered from schizophrenia [22], additionally, its absence was more common than controls [23].…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, pacientes com síndrome de Chiari tipo II apresentam um aumento global da AI, e sua posição próxima ao aqueduto cerebral sabidamente contribui para uma maior pressão no terceiro ventrículo 5 . Também existem correlações entre a ausência da AI em pacientes com Epilepsia do Lobo Temporal Mesial 2 e Esquizofrenia 3 , bem como achados histológicos e de DTI (Diffusion Tensor Imaging) sugestivos de que haja atividade na Aderência Intertalâmica 6,7 .…”
Section: Introductionunclassified